Taṭbīq Namūdhaj LOK-R fī Taʿlīm Qawāʿid al-Lughah al-ʿArabīyah fī al-Madrasah al-Thānawīyah Nūr al-Islām Lumbūk al-Wusṭá - Aziz, Abdul; Mujiburrahman Nur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research is motivated by the lack of interest and understanding of Madrasah Aliyah students in learning Arabic Qawa'id. The dominant traditional learning model with lectures and rote memorization of rules without context is deemed less effective. This study aims to determine the application of the LOK-R Model (Literacy, Orientation, Collaboration, Reflection) in Arabic Qawa'id learning to enhance student engagement and understanding. This research employs a qualitative approach with a case study research type. Data were collected through observation, interviews with Arabic language teachers and involved students, and document analysis of the Lesson Plan (RPP). Data analysis was conducted descriptively qualitative based on the Miles and Huberman model. The results of this research show that the application of the LOK-R model consists of four stages. The first stage is the literacy stage, where students become familiar with the concept through analyzing relevant texts. In this stage, students read and analyze texts to extract examples related to the rule. The second stage is the orientation stage. In this stage, the teacher presented the concept through a systematic understanding and clear explanation of Arabic grammar rules, focusing on applied examples from the texts analyzed by the students in the literacy stage. In the third stage, which is the collaboration stage, students deepen their understanding of the material through joint discussions and analysis. In the fourth stage, the reflection stage, students reflect on the material they have studied in terms of their understanding, comprehension, and application of it, in addition to identifying the difficulties they faced and how to overcome them. أجري هذا البحث لسبب قلة اهتمام طلاب الفصل الثاني بالمدرسة الثانوية نور الإسلام لمبوك الوسطى بتعلم قواعد اللغة العربية وضعف فهمهم لها. وقد ظهرت هذه المشكلة نتيجة اعتماد أساليب التدريس التقليدية التي ترتكز على الحفظ. يهدف هذا البحث إلى معرفة تطبيق نموذج LOK-R في تعلم قواعد اللغة العربية. استخدم هذا البحث المنهج النوعي بنوع دراسة الحالة. تم جمع البيانات من خلال الملاحظة، والمقابلات مع معلمي اللغة العربية والطلاب، وتحليل وثائق خطة تنفيذ الدر (RPP). واستخدم الباحث نموذج مايلز وهوبرمان لتحليل البيانات. وأما نتائج هذا البحث أن تطبيق نموذج LOK-R يتكون من أربعة مراحل؛ المرحلة الأولى مرحلة محو الأمية، حيث يتعرف الطلاب على المفهوم من خلال تحليل النصوص ذات الصلة، يقرأ الطلاب في هذه المرحلة النصوص وتحليلها لاستخراج الأمثلة المتعلقة بالقاعدة. والثانية مرحلة التوجيه، في هذه المرحلة قدم المدرس المفهوم فهماً منظماً وشرحًا واضحًا لقواعد اللغة العربية، مع التركيز على الأمثلة التطبيقية من النصوص التي حللها الطلاب في مرحلة محو الأمية. والثالثة مرحلة التعاون، تعمق فهم الطلاب للمواد من خلال المناقشات والتحليلات المشتركة، والرابعة مرحلة التأمل، تأمل الطلاب المادة التي درسوها من جانب فهمهم واستيعابهم وتطبيقهم لها، بالإضافة إلى تحديد الصعوبات التي واجهوها وكيفية التغلب عليها.